2015
DOI: 10.3176/proc.2015.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance-related patterns in unstable rocky benthic habitats of the north-eastern Baltic coast

Abstract: Abstract. Distinct patterns of benthic flora and fauna are produced when unstable rocky substrata are disturbed by water motion. This study investigated occurrence of disturbance-related patterns in benthic boulder habitats on the north-eastern Baltic coast. Sessile assemblages, mostly algae on tops of boulders and barnacles and bryozoans underneath, were found to differ between small (50-150 cm 2 upperside surface area) and large (200-800 cm 2 ) boulders. Densities of motile gammaridean amphipods were negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Similarly to our results (Fig. 6), Grzelak & Kuklinski (2010) found a higher probability of the presence of organisms on large and medium rocks than on small rocks, confirming that in the Baltic Sea coastal habitat larger rocks are more stable and likely to provide a better substrate for community development (Liversage & Kotta, 2015). In higher salinity, where Ordination derived from Bray-Curtis measures based on square-root transformed abundance data for each subsample per sampling location.…”
Section: Discussionsupporting
confidence: 71%
“…Similarly to our results (Fig. 6), Grzelak & Kuklinski (2010) found a higher probability of the presence of organisms on large and medium rocks than on small rocks, confirming that in the Baltic Sea coastal habitat larger rocks are more stable and likely to provide a better substrate for community development (Liversage & Kotta, 2015). In higher salinity, where Ordination derived from Bray-Curtis measures based on square-root transformed abundance data for each subsample per sampling location.…”
Section: Discussionsupporting
confidence: 71%
“…On intertidal reefs consisting of unstable substrata such as boulders, the patterns caused by disturbance are well known [21, 27, 28]. In this study, patterns were observed of disturbance, and the provision of new ecological resources via disturbance, on a rocky shore in South Australia characterised by large boulders.…”
Section: Introductionmentioning
confidence: 91%
“…Ecological processes such as competition, predation and grazing can leave distinct patterns, allowing inference of the spatiotemporal extent of those processes by observing indicative patterns [ 24 26 ]. On intertidal reefs consisting of unstable substrata such as boulders, the patterns caused by disturbance are well known [ 21 , 27 , 28 ]. In this study, patterns were observed of disturbance, and the provision of new ecological resources via disturbance, on a rocky shore in South Australia characterised by large boulders.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they are important contributors to coastal biodiversity and high benthic production. These habitats provide valuable feeding areas, and spawning and nursing grounds for fish [1][2][3]. Human impact on coastal habitats is increasing and benthic communities living in these environments are particularly affected [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%